2006
DOI: 10.1002/jcb.21076
|View full text |Cite
|
Sign up to set email alerts
|

1[alpha],25‐dihydroxyvitamin D3enhances annexin II dependent proliferation of osteoblasts

Abstract: Cells experience a variety of physiological and non-physiological stresses and consequently have appropriate mechanisms to deal with such deviations from homeostasis. Particularly subject to mechanical stress and shear forces are the cells that make up the bones. Osteoblastic cells can interpret this stress as a stimulus for proliferation; however, the molecular mechanisms underlying this phenomenon are poorly understood. We have identified annexin II as being specifically upregulated in mechanically stressed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Some proteins (as ANXA2 or HSBP1) play a role in ACTB regulation, influencing both the homeostasis of gingival connective tissues and the evolution of the wound‐healing process (Maier et al. , Friedl & Wolf , Cáceres et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…Some proteins (as ANXA2 or HSBP1) play a role in ACTB regulation, influencing both the homeostasis of gingival connective tissues and the evolution of the wound‐healing process (Maier et al. , Friedl & Wolf , Cáceres et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…It is interesting to speculate that DBP also may interact with the cell surface MARRS receptor for delivery of vitamin D. Indeed, we have reported that active vitamin D (but not the inactive 25-hydroxy form), when bound to DBP, completely eliminates the C5a chemotactic cofactor function, an effect that is dependent upon cell surface alkaline phosphatase (AP) activity [30]. Furthermore, studies have shown that both cell surface AP [39] and perhaps the MARRS receptor [40] interact with annexin A2, a molecule that we previously demonstrated binds DBP and is required for C5a chemotactic cofactor activity [27]. Thus, it is conceivable that cell localization sequences in DBP target the protein to a cell surface protein complex for delivery of vitamin D sterols.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously demonstrated that Annexin A5 (AnxA5) is central to osteoblast mechanotransduction, as chemical or antibody inhibition of AnxA5 significantly decreased fluid shear stress-induced Ca 2+ signaling and gene expression [6]. Another annexin isoform, annexin A2 (AnxA2), is expressed in cells of the osteoblast lineage including rat calvarial osteoblasts [7], human long bone osteoblasts [8], mouse MC3T3-E1 [8-10] rat UMR-106 cells [9], rat ROS 24/1 cells and human osteosarcoma Saos-2 and SaOSLM2 cells [11, 12]. Anxa2 is also expressed in mesenchymal stem cells that have osteogenic potential, including those derived from human bone marrow [13, 14] and human umbilical cord [15].…”
Section: Introductionmentioning
confidence: 99%